Efektivitas Pembelajaran Daring Wawasan Kebangsaan - Afnan Fuadi (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2021)
[EFFECTIVENESS OF NATIONAL INSIGHTS ONLINE LEARNING]. This study aims to determine the effectiveness of national insight online learning in Basic Training for Civil Servant Candidate Group II 2020 at Apparatus Training Center of Ministry of Maritime Affairs and Fisheries. This study was a quasi experimental research with a quantitative approach. The data was collected using an assignment sheet, questionnaire, and interview. The learning effectiveness indicator was all participants get a minimum post test score of 80 and at least 80%. The research sample was all participants of Basic Training for Civil Servants Group II 2020 with the total number of 16 people. The result shows that the pre-test mean score is 84.5 and the post-test mean score is 97.5, indicating an increase of 15.4%. Based on the questionnaire result, it is found that the online learning method of Public Ethics is effective in achieving the learning objectives. National insight online learning of Basic Training for Civil Servants Candidates with all its strengths and weaknesses is considered effective in achieving learning objective, therefore, it can be continued in both new normal and normal condition